PENGENALAN DAN PELATIHAN PROGRAM MICROSOFT OFFICE MENGGUNAKAN MICROSOFT POWERPOINT BAGI GURU DI SMK AL-MADANI PONTIANAK - Barry Ceasar Octariadi (Jurnal Buletin Al-Ribaath, 2018)
The mastering of Information technology and communication (TIK) for teacher is needed to improve the competency of teacher in giving the subject to the students at their schools. Besides, the competency in IT field could be used in everyday activity such as report making, presentation making and others. Microsoft office is a software package made by Microsoft Corporation which is designed to make work easier. This activity will be focused in introducing and training for using Microsoft Power Point as the presentation tools, due to its ability for showing text, picture and video and other features, which can be used to attract students attention in teaching activity. With this helpful software, we aim to conduct the training about Microsoft Power Point to the educators, more specific to teachers in Al-Madani Vocational High School (SMK Al-Madani) Pontianak. This activity hopefully could give them more knowledge about the useful of Microsoft Power Point, and it could be used more effectively and efficiently in education.